Analysis of the Influence of Parenting on the Incidence of Stunting in Toddlers - A'ini, Syarifah; Susanti, Nofi; Agustina, Dewi (Indonesian Journal of Global Health Research, 2024)
In 2023, there will be an increase in the prevalence of stunting in the Puskesmas working area, decreasing from 31 stunted toddlers to 35 stunted toddlers compared to the previous year. Meanwhile, the target for reducing the stunting rate in Medan City by 2024 is 14.92%. The research aims to analyze the influence of parenting styles on the incidence of stunting in the area, with a focus on parental practices/support for children in feeding practices personal hygiene practices, and environmental sanitation. This research uses a quantitative approach with an observational case-control design. The sample size was 70 respondents who were divided into two groups, namely 35 respondents in the case group and 35 respondents in the control group. The results of this study show that there is an influence between parental practices/support in providing food (p-value=0.000) and personal hygiene/hygiene practices and environmental sanitation on the incidence of stunting in the working area of the Terjun Community Health Center (p-value=0.006) with an Odds value The ratio (OR<1) indicates that these factors have a weak or protective influence on the incidence of stunting. From the results of this research, it can be concluded that parental practices/support in providing food and personal hygiene practices and environmental sanitation influence the incidence of stunting, but positively as protective factors against the incidence of stunting in the working area of the Terjun Community Health Center.